Structural health monitoring of green concrete - Xu, Jun. (2012)
Nowadays, using recycled aggregates to produce concrete, which is an environmental friendly and economical approach, is becoming more and more popular in construction industry. However, properties of concrete which consist of recycled aggregates may not be as good as what we predicted. Besides, quality of recycled aggregates also affects the properties of recycled aggregates concrete. Therefore, test on effects of recycled aggregates on concrete is important.